Mortality due to cardiovascular diseases in the Americas by region, 2000-2009 - Gawryszewski, Vilma Pinheiro; Souza, Maria de Fatima Marinho de (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Cardiovascular diseases are the leading cause of death worldwide. The aim here was to evaluate trends in mortality due to cardiovascular diseases in three different regions of the Americas. DESIGN AND SETTING: This was a time series study in which mortality data from three different regions in the Americas from 2000 to the latest year available were analyzed. METHODS: The source of data was the Mortality Information System of the Pan-American Health Organization (PAHO). Data from 27 countries were included. Joinpoint regression analysis was used to analyze trends. RESULTS: During the study period, the age-adjusted mortality rates for men were higher than those of females in all regions. North America (NA) showed lower rates than Latin America countries (LAC) and the Non-Latin Caribbean (NLC). Premature deaths (30-69 years old) accounted for 22.8% of all deaths in NA, 38.0% in LAC and 41.8% in NLC. The trend analysis also showed a significant decline in the three regions. NA accumulated the largest decline. The average annual percentage change (AAPC) and 95% confidence interval was -3.9% [-4.2; -3.7] in NA; -1.8% [-2.2; -1.5] in LAC; and -1.8% [-2.7; -0.9] in NLC. CONCLUSION: Different mortality rates and reductions were observed among the three regions.